Keterampilan Psikologis untuk Meningkatkan Stabilitas Emosi Pengguna Napza - Yanwar Arief; MG. Adiyanti (JIP (Jurnal Intervensi Psikologi), 2010)
Drug abuser has emotional instability such as anxiety, anger, sadness, shame, and confusedness. Psychological skill training was aimed at increasing drug abuser's emotional stability. The participants were 14 drug abusers divided non randomly into 2 groups, experiment and control groups. This training was held in 6 sessions and the duration for each session is approximately 2 to 3,5 hours. The design of this research used pre test and post test control group design. The emotional stability was measured by emotional stability scale. Data analysis used statistic non parametric test, Mann Whitney. The result shows that there's gained score difference between pre test and post test experiment and control groups, with z value z=-2,179 andp=0,0291 (p<0,05). Thus, psychological training proved can increase emotional stability for drug abusers.Â Key word: Psychological skill, emotional stability, drug abusers